Understanding what one reads III : essays on the Gospels and Paul (2011-2014) - Lambrecht, Jan; Koperski, Veronica (2015)
This third volume of 'Understanding What One Reads' includes forty-two studies of the New Testament. The three volumes cover 1992-2003 (I); 2003-2011 (II) and 2011-2014 (III). Though for the most part the content of this third volume falls under the category of responses to recent scholarly books or articles, some conference papers directed toward more general audience are included. In this volume Lambrecht continues his defense of the thesis of Mark's dependence on Q. In addition, a major subdivision reflects on Paul. At the end of this third book there is provided a canonical list of his English articles written between 1992-2014 from 'Collected Studies on Pauline Literature and the Book on Revelation' (Rome, 2001) as well as those in the three volumes of 'Understanding What One Reads'. These additional features will facilitate endeavors to follow the chronological development of Professor Lambrecht's thought.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc